Mural endocarditis - by default - Patel, A.; Kakooza, D.; Kalk, T.; Tsabedze, N. (SA Heart Journal, 2021)
We report on a case of a 33-year-old female patient with known adult congenital heart disease in the form of a coronary cameral fistula who, on prior presentation, had refused treatment and subsequently defaulted follow-up, but unfortunately developed a serious and rare complication. She presented with non-specific neurological symptoms of transient visual loss and headaches. Clinical examination revealed aortic regurgitation with peripheral features of infective endocarditis. This was confirmed with transthoracic echocardiogram, but additionally, we found mural endocarditis of the right atrial posterior wall. An initial CT brain scan and ophthalmology assessments were negative, blood cultures were positive and confirmed infective endocarditis, and she was referred for urgent cardiothoracic surgery. Unfortunately, she had further complications with a large intracranial haemorrhage which ultimately led to her death. This case illustrates a rare entity with disastrous complications.